Assessment of the Digital Competence of Future Teachers from a Gender Perspective [Evaluación de la Competencia Digital de Futuros Docentes Desde Una Perspectiva de Género] - Silva-Quiroz, J (Ibero-American Association for Distance Higher Education (AIESAD), 2022)
Digital competence is one of the key competencies to achieve a digitally literate citizenship. In university education, this competence is relevant in the curriculum, which should be developed based on this specific professional context and also in a way that allows enrichment the academic training and personal development of each student. Digital competence acquires special relevance to develop digital competence among teachers, for which it is necessary to work on it during the first years of initial teacher training. This article presents the results of research developed with first-year Pedagogy students from three Chilean public universities. The purpose of the study was to determine the level of digital competence among students and to make visible the influence of gender on the levels of achievement in this competence through the application of the assessment instrument COMPDIG-PED, based on the European Framework of Digital Competences (DIGCOMP). A quantitative methodology was used to carry out the research with a stratified representative sample of 817 students. The results show that statistically significant differences are identified in the areas of Communication and Collaboration, Creation of Digital Content and Problem Solving, in which men scored higher than women. This issue highlights the digital gender gap in the initial training of future teachers in the context of the study. © 2022, Ibero-American Association for Distance Higher Education (AIESAD). All rights reserved.